Helicobacter pylori cagA, vacA and iceA genotypes in northern Thai patients with gastric disease - Linpisarn S. (2014)
Hellcobacter pylori, a common infectious bacterium, has been linked to chronic gastritis, peptic ulcer and gastric cancer. Gastric biopsy specimens were obtained from 58 northern Thai patients with gastritis, 28 with gastric ulcer, 45 with duodenal ulcer and 4 with gastric cancer. cagA, vacA s1 and iceA gene was found in 88, 98, and 89% of the specimens, respectively. For vacA, the frequency of subtype s1a, sic and combined s1a and sic was 40, 16, and 41%, respectively. The frequency of subtype s1a/m1 and s1a/s1c/m1 was 27 and 20%, respectively. Fifty-three patients (39%) were infected with multiple vacA genotypes but there was no association with clinical outcome. cagA positive and mixed vacA s1a and sic strains were found in significantly more cases of duodenal ulcer than gastritis (p<0.05). For iceA, subtype icaA1 reached a frequency of 60%, whereas subtype iceA2 was only 24%.